Sosialisasi Bahaya Resistensi Antibiotik Terhadap Penyakit Infeksi Pada Masyarakat - Ismail Rahman; Amran Nur (STKIP Andi Matappa, 2022)
The purpose of this socialization is to reduce the risk of antibiotic drugs becoming resistant to infectious diseases that may occur in the community, where the public can study various antibiotic preparations and how to use them to achieve the desired effect. This activity is carried out in the form of counseling, the implementation stage starts from field trips. After getting permission and approval from Marikurubu local village Ternate city, the distribution of invitations to the local community was carried out. In this case, teaching the public how to form drug preparations, how to get and use antibiotics, followed by question and answer sessions, and finally the distribution of leaflets on antibiotics as a guide. As a result of the implementation of this devotional activity, the community has begun to understand the dangers of antibiotic resistance to infectious diseases, seen from enthusiastic community questions and information support from leaflets that have been shared. With the implementation of this activity, the community has learned about how to use and how to get antibiotics correctly, thereby reducing the risk of antibiotic resistance to infectious diseases that may occur in the community.